VISUALISASI DATA COVID-19 DI INDONESIA - Zakaria, nabil (PT. ZIVANA CENDEKIAWAN BANGSA, 2024)
Thepandemicin2020hasspreadaroundtheworldwiththeunprecedentedSARS-CoV-2 outbreak,thistypeofcoronaviruscausingthemassivelygrowingCOVID-19pandemic. CasesofpatientsdetectedwithCOVID-19havenowreached627,195,515casesworldwide. InIndonesia,positivepatientswithCOVID-19havereached6,464,962and158,380patients havedied.Thisstudyaimstoproduceavisualizationoroverviewofdatabasedonthe distributionofCOVID-19casesinIndonesia.Inconductingtheanalysis,adatasetis needed,inthisstudyusingadatasetofCOVID-19casesfrom March1,2020toJune30, 2020.ThisresearchusestheBusinessIntelligence(BI)methodtoconvertoperational, transactionaldataintousefulinformationforstakeholders,whilevisualizationofdatathat hasbeenprocessedusingtheMicrosoftPowerBIapplication.Thevisualizationresultson thePowerBIdashboardfoundthatthehighestnumberofpositiveCOVID-19caseswasin EastJavaprovincewithatotalof12,807withavulnerabilityofMarch1,2020toJune30, 2020,withtheapplicationofthesedatasetsexpectedtohelpstakeholdersinmaking